La correspondencia del hombre práctico. Los usos epistolares de la nobleza española del Siglo de Oro a través de seis años de cartas del tercer conde de Fernán Núñez (1679-1684) - Bouza, Fernando (Cuadernos de Historia Moderna, 2006)
Francisco Gutiérrez de los Ríos y Córdoba, 3rd Earl of Fernán Núñez, well known as an author (El hombre práctico. Seville?: 1686), also devoted his energies to letter-writing. He wrote almost six thousand letters from 1679 to 1684, setting up a varied correspondance which now can be studied thanks to a very single source, the daily six-year account of all his letters. This source provides a huge amount of information about the uses practised by early modern Hispanic and European nobles and it shows how the aristocratic letter-writing customs reveal a distinctive type of sociability based on manuscript correspondance.